International School Social Work: Building Networks and Relationships - Leticia Villarreal Sosa (International Journal of School Social Work, 2020)
This editorial discusses the importance of international collaborations in the development of school social work. As school social workers, we face common issues in the schools that can be effectively addressed by the sharing of information and resources across national borders and by supporting the development of interventions and indigenous practices that are best suited for local contexts. The SSWAA school social work practice model is reviewed and questions posed about how extending this model to address global school social work practice.
Keywords: international school social work; international collaboration; school social work model